Assessment of Farmers’ Knowledge on Nutrition and Nutrition-Sensitive Agriculture - P N Fatheen Abrar; Satyapriya; Barua, Sukanya; Mahra, Girijesh Singh; Bishnoi, Sitaram; Ray, Mrinmoy; Khan, Shakeel Ahmad; Roy, Surjya Kanta; Ranjan, Amandeep; Nath, Rajat Kumar (Indian Journal of Extension Education, 2025)
Nutritional knowledge plays a vital role in shaping the dietary behaviour of individuals and communities. This study assessed farmers’ knowledge of nutrition and nutrition-sensitive agriculture (NSA) in the southern Indian states of Kerala and Karnataka during 2024-25. A standardized knowledge test comprising 26 statements was developed and administered to a sample of 300 respondents. Statistical analyses, including Welch’s t-test, Welch’s ANOVA, and the Games-Howell post-hoc test, were used to compare knowledge scores across states and districts. In addition, regression analysis was employed to examine the relationship between farmers’ knowledge and socio-economic characteristics. State- and district-level comparisons indicated that farmers from Kerala had higher knowledge levels than those from Karnataka. Regression analysis revealed that factors such as education, gender, age, source of information, number of trainings attended, and family size significantly influenced farmers’ knowledge. These disparities underscore the necessity of awareness campaigns and capacity-building programs on nutrition and NSA, particularly through educational institutions, rural organizations, and mass media platforms.